2017
DOI: 10.1002/slct.201701625
|View full text |Cite
|
Sign up to set email alerts
|

Fe(CO)5Catalyzed [2+2+1] Cycloaddition of Alkyne, Carbodiimide and CO for the Synthesis of 5-Iminopyrrolones

Abstract: Under photolytic conditions, mixture of a terminal alkyne, a carbodiimide and CO, in presence of Fe(CO)5, undergoes [2+2+1] cocyclization to form 5‐iminopyrrolone. Its formation has been shown to occur via a stable tetracarbonyl(2‐aryl/alkyl maleoyl)iron intermediate. Addition of carbodiimide to the intermediate leads to the formation of 5‐iminopyrrolone. This work highlights the role of Fe(CO)5 as a catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…put forward a [2 + 1 + 1] cycloaddition of terminal alkyne 51 , CO and carbodiimide 53 for 5‐iminopyrrolones 54 . [ 47 ] The three‐component reaction resulted in the product in moderate to good yields (Scheme 16). The exploration of substrates revealed that the electron‐donating substituent at para ‐ position increased the yield while methyl group at the ortho position decreased.…”
Section: Classificationmentioning
confidence: 99%
“…put forward a [2 + 1 + 1] cycloaddition of terminal alkyne 51 , CO and carbodiimide 53 for 5‐iminopyrrolones 54 . [ 47 ] The three‐component reaction resulted in the product in moderate to good yields (Scheme 16). The exploration of substrates revealed that the electron‐donating substituent at para ‐ position increased the yield while methyl group at the ortho position decreased.…”
Section: Classificationmentioning
confidence: 99%
“…In 2017, Mathur and co‐workers reported a one‐pot multi‐component cycloaddition reaction of alkynes, carbodiimides, and CO for the synthesis of 5‐iminopyrrolones by using Fe(CO) 5 as the pre‐catalyst (Scheme 18). [43] As proposed in this work, Fe(CO) 5 loses one CO to form [Fe(CO) 4 ] under light irradiation, which may be the true catalytic species. Then, the subsequent coordination with one alkyne and insertion of two CO leads to the formation of a tetracarbonyl(2‐aryl/alkyl‐maleoyl) iron intermediate, which undergoes coordination with carbodiimide and releases one CO.…”
Section: Light‐induced Generation Of Active Iron Catalystsmentioning
confidence: 73%